2007
DOI: 10.1038/sj.leu.2404659
|View full text |Cite
|
Sign up to set email alerts
|

The quality of molecular response to chemotherapy is predictive for the outcome of AML1-ETO-positive AML and is independent of pretreatment risk factors

Abstract: The outcome of 45 AML1-ETO-positive acute myeloid leukemia (AML) patients was analyzed with special emphasis on the quality of molecular response to therapy. Patients received double induction therapy, either 6-thioguanine, cytarabine, and daunorubicin (TAD9)/high-dose cytosine arabinoside plus mitoxantrone (HAM) or HAM/HAM, followed by consolidation therapy (TAD9) according to the AML-Cooperative group 92 trial (AMLCG92) and AML-Cooperative group 99 trial (AMLCG99). All cases underwent cytomorphological, cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 26 publications
2
40
1
Order By: Relevance
“…This did not translate into different survival, probably because patients in CR with <3-log reduction after the first consolidation therapy proceeded to allogeneic HSCT instead of two further HD-AraC consolidation cycles. Previous studies demonstrated a negative prognostic impact on survival of increased MRD levels after induction and after consolidation therapy (Krauter et al, 2003;Schnittger et al, 2003;Weisser et al, 2007) or persistence or reocurrence of positive MRD level after end of therapy (Yin et al, 2012) for patients with CBF leukaemias.…”
Section: Cbf Leukaemiasmentioning
confidence: 99%
“…This did not translate into different survival, probably because patients in CR with <3-log reduction after the first consolidation therapy proceeded to allogeneic HSCT instead of two further HD-AraC consolidation cycles. Previous studies demonstrated a negative prognostic impact on survival of increased MRD levels after induction and after consolidation therapy (Krauter et al, 2003;Schnittger et al, 2003;Weisser et al, 2007) or persistence or reocurrence of positive MRD level after end of therapy (Yin et al, 2012) for patients with CBF leukaemias.…”
Section: Cbf Leukaemiasmentioning
confidence: 99%
“…Several small, retrospective cohort studies have suggested that monitoring MRD using real-time quantitative reverse transcriptasepolymerase chain reaction (RQ-PCR) may identify patients at high risk for relapse. [19][20][21][22][23][24] Two studies found that a reduction in MRD (RUNX1/RUNX1T1 transcript levels) of ,3 logs compared with pretreatment levels was a significant predictor of relapse after 2 courses of consolidation or within 3 to 4 months after achieving complete remission (CR). 19,21 Because HSCT exhibits the strongest anti-leukemia effects, we hypothesize that HSCT can decrease the relapse rate and improve the outcomes of patients with t(8;21) AML who are classified as high risk according to their MRD status.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Common targets for polymerase chain reaction (PCR)-based MRD detection are mainly fusion transcripts, eg, RUNX1-RUNX1T1 (previously AML1-ETO), CBFB-MYH11, PML-RARA, and MLL-gene fusions. [1][2][3][4][5][6][7][8] Because fusion genes are present in only approximately 25% of AML, further markers like MLL-PTD, FLT3-LM, 7,9 and ectopic expression of WT1 and EVI1 have recently been established as additional sensitive and valuable targets. [10][11][12] Our potential to further expand the number of patients with AML that may benefit from analysis of MRD is closely dependent upon the availability of new molecular markers that allow us to identify new leukemia entities in the context of the poorly characterized group of AML with normal karyotype (NK; 40%-50% of cases in multicenter studies).…”
Section: Introductionmentioning
confidence: 99%